Pica Behavior Resistant to Pharmacologic and Behavioral Treatment - David Ming Gui Tan; Aida Farina Ismail; Sharynol Emryan bin Ayub; Walton Wider; Noor Melissa Binti Nor Hadi; Sylas Sebastian Neela Sekhar; Mohd Nazri Mohd Daud; Natchana Bhutasang (Malaysian Journal of Psychiatry Ejournal, 2025)
To elucidate the rarity of pica in a patient with schizophrenia and intellectual disability and to highlight the complexities involved in managing this rare behavior through pharmacological and behavioral interventions. We present the case of Mr. H, a 67-year-old male with schizophrenia and intellectual disability, who exhibited persistent patterns of eating nonnutritive items 12 years after being treated with several first-generation antipsychotics. Although later diagnosed with anemia, there was no temporal relationship between his behavior and anemia. This case report highlights the challenges in understanding the causes of pica and its relationship with psychiatric diagnoses and psychotropic medication use. It points to the necessity for an in-depth examination of complex behaviors, especially in patients who are unable to articulate their motivations behind challenging behaviors. Pica is often overlooked in mental health care, and this case emphasizes the urgent need for more research to improve our knowledge and treatment of this condition.